2015
DOI: 10.3747/co.22.2689
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Palliative Treatments in Stage III Non-Small-Cell Lung Cancer: What Contribution Is Made by Time-Dependent Changes in Tumour or Patient Status?

Abstract: IntroductionStage iii lung cancer is the most advanced stage of lung cancer for which the potential of curative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…One recent Canadian study found that approximately one-half of this population is not treated curatively, with weight loss and performance status heavily affecting treatment intent. 14,15 It is beyond the scope of this guideline update to define curability for stage III NSCLC, but knowing that these patients are frequently treated with palliative intent, we view RCT data on how this treatment should be delivered as valuable. Ultimately, we leave it to the discretion of the prescribing physicians to determine parameters for curability, acknowledging that poor PS, weight loss, and inability to achieve dosimetric goals likely provide the best guidance.…”
Section: Narrativementioning
confidence: 99%
“…One recent Canadian study found that approximately one-half of this population is not treated curatively, with weight loss and performance status heavily affecting treatment intent. 14,15 It is beyond the scope of this guideline update to define curability for stage III NSCLC, but knowing that these patients are frequently treated with palliative intent, we view RCT data on how this treatment should be delivered as valuable. Ultimately, we leave it to the discretion of the prescribing physicians to determine parameters for curability, acknowledging that poor PS, weight loss, and inability to achieve dosimetric goals likely provide the best guidance.…”
Section: Narrativementioning
confidence: 99%
“…A significant proportion of locally-advanced non-small cell lung cancer (NSCLC) patients are ineligible for standard of care radical treatment. Recommendations suggest 6-7 weeks of concurrent chemoradiotherapy [1,2], but due to competing comorbidities, logistic issues associated with daily attendance over many weeks and the toxic nature of treatment, almost half of patients do not receive curative treatment [3][4][5] and up to 21% receive no treatment whatsoever [6,7]. The situation was similar for early-stage NSCLC patients until the advent of stereotactic body radiotherapy (SBRT).…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, the median age of the patients in our series was 61.23 years in the literature younger than in Robinson and Shamsi series with a median age of 68 years and 70 years respectively[22 -81]; collaborator found an average age of 68 years in Ontario[3] and found an average age of 70 years[4].The reasons for the palliative treatment of lung cancer in our center were essentially due essentially to dosimetric constraints: large tumor volume; localization close to the spinal cord marrow and the deterioration of performance status (>2) and pulmonary function of our patients. Thus, these reasons are comparable to those found by Sundstrom and collaborators in a study involving 421 patients with locally advanced stage III or IV lung tumors treated by palliative radiotherapy, who included patients with disease too advanced for inoperable curative radiotherapy, those with chest symptoms due to a central tumor threatening the airways[5].…”
mentioning
confidence: 52%